Mobile Communications Industry Scenarios and Strategic Implications for Network Equipment Vendors - Hannu Enqvist; Thomas Casey (International Telecommunications Society (ITS), 2010)
Mobile infrastructure markets have changed dramatically during the past years. The industry is experiencing a shift from traditional large-scale, hardware-driven system roll-outs to software and services -driven business models. Also, the telecommunications and internet worlds are colliding in both mobile infrastructure and services domains requiring established network equipment vendors and mobile operators to transform and adapt to the new business environment. This paper utilizes Schoemaker's scenario planning process to reveal critical uncertain elements shaping the future of the industry. Four possible scenarios representing different value systems between industry's key stakeholders are created. After this, five strategic options with differing risk and cost factors for established network equipment vendors are discussed in order to aid firm's strategic planning process.
Keywords: 330